Arah Pengembangan Pemikiran Arab-Islam: Tawaran Arkoun pasca Difitisme 1967 - Yuangga Kurnia Yahya (Jurnal Pemikiran Islam, 2022)
This study aims to look at socio-religious conditions in the Arab world after the 1967 Difitism in Arkoun's view. This view then gave birth to various basic assumptions and offers of thought development in order to address the decline of Arab-Islamic thought. This study will highlight two ideas from Arkoun, both are Applied Islamology and its application in understanding the discourse of the Qur'an. This study uses a qualitative method with data collection through literature study. This study shows that Arkoun offers an offer in the form of Applied Islamology, which requires a dialogical relationship between Islamic religious knowledge (ulum al-din) and social science methodology. This is intended to make Islamic religious texts relevant according to the context of the times and the Qur'anic discourse can be understood its relevance in different spaces and times. Arkoun's offer needs to be followed up receptively critically in order to be able to apply it within the framework of thinking about the philosophy of Islamic sciences as a solution to various problems of the people today.AbstrakStudi ini bertujuan untuk melihat kondisi sosial keagamaan di dunia Arab pasca Difitisme 1967 dalam pandangan Arkoun. Pandangan tersebut kemudian melahirkan berbagai asumsi dasar dan tawaran pengembangan pemikiran dalam rangka menyikapi kemunduran pemikiran Arab-Islam. Studi ini akan menyoroti dua ide dari Arkoun, yaitu Islamologi Terapan dan penerapannya dalam memahami wacana al-Qur’an. Studi ini menggunakan metode kualitatif dengan pengumpulan data melalui studi pustaka. Studi ini menunjukkan bahwa  Arkoun memberikan tawaran berupa Islamologi Terapan, yang mensyaratkan hubungan dialogis antara ilmu agama Islam (ulum al-din) dengan metodologi ilmu sosial. Hal ini dimaksudkan untuk membuat teks-teks keagamaan Islam dapat relevan sesuai dengan konteks perkembangan zaman dan wacana al-Qur’an dapat dipahami relevansinya dalam ruang dan waktu yang berbeda. Tawaran Arkoun tersebut perlu ditindaklanjuti secara reseptif kritis untuk dapat mengaplikasikannya dalam kerangka berpikir filsafat ilmu-ilmu keislaman sebagai solusi atas berbagai permasalahan umat saat ini.